2012
DOI: 10.17221/512/2012-pse
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between winter wheat yields and soil carbon under various tillage systems

Abstract: Soil quality and fertility are associated with its productivity, and this in turn is connected to the soil biological activity. To study these effects, well designed long-term field experiments that provide comprehensive data sets are the most applicable. Four treatments (tillage methods) were set up: (1) conventional tillage (CT); (2) no tillage (NT); (3) minimum tillage + straw (MTS), and (4) no tillage + mulch (NTM). Our objective was to assess the relationships between soil microbial characteristics and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
2
14
0
1
Order By: Relevance
“…In the soil from RT and NT plots, the content of organic carbon was significantly higher than in the CT soil (Table 3). Also in investigations conducted by De Vita et al (2007) and Mikanová et al (2012) organic C content in the topsoil was higher in the no-till than in the ploughing system. According to Reeder (2000), the ploughing system accelerates mineralization of organic matter and hence a lower content of organic C is observed in these plots than in the soil from no-till system.…”
Section: Resultsmentioning
confidence: 85%
“…In the soil from RT and NT plots, the content of organic carbon was significantly higher than in the CT soil (Table 3). Also in investigations conducted by De Vita et al (2007) and Mikanová et al (2012) organic C content in the topsoil was higher in the no-till than in the ploughing system. According to Reeder (2000), the ploughing system accelerates mineralization of organic matter and hence a lower content of organic C is observed in these plots than in the soil from no-till system.…”
Section: Resultsmentioning
confidence: 85%
“…Thus, concentration of salts was decreased in the upper layers which favored the growth of plant and ultimately a significant increase in rice grain was observed (Ghafoor et al 2008). A recent study demonstrated that there was a statistically significant correlation (P ≤ 0.01) between the grain yields and organic C content of soil after application of organic amendments to soil (Mikanová et al 2012). The combined application of farm manure and mineral fertilizer could induce an increase in the humus content, nitrogen, and available phosphorus and potassium levels (Gondek andFilipek-Mazur 2005, Verma et al 2012).…”
Section: Resultsmentioning
confidence: 98%
“…It is well known that soil quality and fertility are connected to the biological activity of soil (Mikanová et al 2012).…”
mentioning
confidence: 99%